Supervisor Discretion in Target Setting: An Empirical Investigation - Bol, Jasmijn C.; Keune, Timothy M.; Matsumura, Ella Mae; Shin, Jae Yong (The Accounting Review, 2010)
ABSTRACT: In a setting in which corporate headquarters dictates total sales targets, we study how supervisors allocate sales targets to individual stores. Specifically, we analyze whether supervisors strategically use discretion in the target-setting process to address compensation contracting issues. We first examine whether supervisors use discretion to manage compensation risk. The results are consistent with the agency-theoretic prediction that supervisors provide easier targets to stores facing higher levels of store-specific risk. Next, we examine whether discretion is used to mitigate fairness concerns. The results suggest that, consistent with behavioral arguments, supervisors use discretion to deal with fairness issues, even if the area of the supervisor’s discretion is not the source of the fairness concerns. Finally, we analyze whether supervisors use discretion in the target-setting process to reduce their potential confrontation costs. Consistent with research in psychology, we find that supervisors provide easier targets to store managers with relatively higher hierarchical status.